2005
DOI: 10.1007/s10549-005-9015-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cell-of-origin breast tumor subtypes in inflammatory breast cancer by gene expression profiling

Abstract: Inflammatory breast cancer (IBC) is an aggressive form of locally advanced breast cancer with high metastatic potential. Most patients have lymph node involvement at the time of diagnosis and 1/3 of the patients have distant metastases. In a previous study, we demonstrated that IBC is a distinct form of breast cancer in comparison with non-IBC. The aim of this study was to investigate the presence of the different molecular subtypes in our data set of 16 IBC and 18 non-IBC specimen. Therefore, we selected an '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
54
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 31 publications
17
54
1
1
Order By: Relevance
“…Using cDNA microarrays, Bertucci et al (2004) and Van Laere et al (2005) identified gene-expression signatures associated with the IBC phenotype. Using the same expression data sets, both studies demonstrated the presence of the same cell-of-origin breast cancer subtypes in IBC (Bertucci et al, 2005;Van Laere et al, 2006a), as was originally described for non-IBC (Perou et al, 2000). In depth analysis of genes differentially expressed between breast tumour samples from patients with IBC and other breast tumour samples revealed a potential hyperactivation of NF-kB in IBC (Van Laere et al, 2005), which was validated and confirmed in an independent study (Van Laere et al, 2006b).…”
supporting
confidence: 67%
See 3 more Smart Citations
“…Using cDNA microarrays, Bertucci et al (2004) and Van Laere et al (2005) identified gene-expression signatures associated with the IBC phenotype. Using the same expression data sets, both studies demonstrated the presence of the same cell-of-origin breast cancer subtypes in IBC (Bertucci et al, 2005;Van Laere et al, 2006a), as was originally described for non-IBC (Perou et al, 2000). In depth analysis of genes differentially expressed between breast tumour samples from patients with IBC and other breast tumour samples revealed a potential hyperactivation of NF-kB in IBC (Van Laere et al, 2005), which was validated and confirmed in an independent study (Van Laere et al, 2006b).…”
supporting
confidence: 67%
“…The presence of different breast cancer cell-of-origin subtypes has been repeatedly observed in IBC (Bertucci et al, 2005;Van Laere et al, 2006a). We have shown that IBC primarily segregates into the basal-like or ErbB2-overexpressing subgroups (Van Laere et al, 2006a).…”
Section: Identification Of the Cell-of-origin Subtypes In Ibc And Nonmentioning
confidence: 58%
See 2 more Smart Citations
“…The few published mRNA expression profiling studies to date have indicated that transcriptional heterogeneity exists in inflammatory breast cancer as extensively as in noninflammatory breast cancer, and that the established molecular subtypes such as luminal, HER2-positive, and basal-type can be identified in inflammatory breast cancer. [5][6][7][8][9][10][11][12][13][14][15][16] Although some of the studies have demonstrated differences in mRNA expression levels between inflammatory breast cancer and noninflammatory breast cancer samples, a specific inflammatory breast cancer signature cannot be deduced from these studies.…”
mentioning
confidence: 99%